2005
DOI: 10.1111/j.1744-697x.2005.00020.x
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment of surfactant Tween 80 and fibrolytic enzyme influencing volatile fatty acid and methane production of a total mixed ration by mixed rumen microorganisms at in vitro

Abstract: In vitro rumen dry matter degradability, volatile fatty acid (VFA) and methane production were examined in a total mixed ration pretreated with different levels of either commercial cellulolytic enzyme (CCE), the surfactant poly oxyethylene sorbitan monoolate (Tween 80) or both: (i) no pretreatment (Control); (ii) with 1% CCE alone; (iii) with 2% CCE alone; (iv) with 1% Tween 80 alone; (v) with 1% Tween 80 + 1% CCE;(vi) with 1% Tween 80 + 2% CCE; (vii) with 2% Tween 80 alone; (viii) with 2% Tween 80 + 1% CCE; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 30 publications
2
10
1
Order By: Relevance
“…These results are comparable to those obtained by Kim et al. who found that HAc/HPr decreased from 2 to 1.8 by increasing T80 concentration from 1 to 2%, respectively. Glucose +2normalH2O2 HAc +2normalCnormalO2+0.16em4normalH2 Glucose 2 HBu +2normalCnormalO20.16em+0.16em2normalH2 Glucose 0.16em+0.16em2normalH22 HPr 0.16em+0.16em2normalH2O…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…These results are comparable to those obtained by Kim et al. who found that HAc/HPr decreased from 2 to 1.8 by increasing T80 concentration from 1 to 2%, respectively. Glucose +2normalH2O2 HAc +2normalCnormalO2+0.16em4normalH2 Glucose 2 HBu +2normalCnormalO20.16em+0.16em2normalH2 Glucose 0.16em+0.16em2normalH22 HPr 0.16em+0.16em2normalH2O…”
Section: Resultssupporting
confidence: 91%
“…2). These results are comparable to those obtained by Kim et al [35] who found that HAc/HPr decreased from 2 to 1.8 by increasing T80 concentration from 1 to 2%, respectively.…”
Section: Effect Of T80 On the Hp From Pmwsupporting
confidence: 91%
See 2 more Smart Citations
“…Before use, the coconut oil was emulsified in a 1:99 v/v aqueous solution of Tween 80 (Sigma–Aldrich, St. Louis, MO, USA) to allow its homogenous dispersal in the mixture inoculum. Tween 80 has previously been shown to have a minimal and inconsistent effect on biohydrogenation and methane production . Therefore, Tween 80 was not expected to have a significant effect on ruminal fermentation and no Tween 80‐only control was used.…”
Section: Methodsmentioning
confidence: 99%